Implementasi Metode Sorogan dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SMK Ihyaul Ulum Gresik - Najiyah, Mir Atun; Najib , Muhammad; Ahmad, Nur Fatih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
Qur’anic education in Islamic boarding schools does not merely emphasize memorization achievements, but also requires leadership that is capable of fostering discipline, role modeling, and sustained spiritual commitment among students. In this context, charismatic leadership plays a strategic role in shaping students’ attitudes, motivation, and consistency throughout the Tahfidz Al-Qur’an process. This study aims to describe the implementation of charismatic leadership in enhancing the success of the Tahfidz Al-Qur’an program at Pondok Pesantren Putri Hafidzul Qur’an Gresik. This research adopts a qualitative approach with a case study design. The research subjects include the pesantren leader (ibu Nyai), male and female teachers (ustadz and ustadzah), and female students (santriwati). Data were collected through participatory observation, in-depth interviews, and documentation studies. The data were analyzed interactively through data reduction, data display, and conclusion drawing in order to obtain a comprehensive and contextual understanding of leadership implementation. The findings indicate that the charismatic leadership of the ibu Nyai is implemented through intensive direct engagement, personal communication, and exemplary conduct in religious practices and discipline. This approach contributes to increased consistency (istiqamah) among students in conducting muroja’ah and maintaining their memorization. Furthermore, the success of the Tahfidz program is not solely supported by memorization targets, but is also strengthened by complementary educational programs, such as the study of classical Islamic texts, which deepen students’ understanding of the meanings of the memorized verses. The implementation of charismatic leadership thus contributes to shaping students who are not only strong in Qur’anic memorization, but also possess moral and intellectual readiness to face contemporary challenges.